Comparative Analysis of Chloroplast Genomes of Four Medicinal Capparaceae Species: Genome Structures, Phylogenetic Relationships and Adaptive Evolution - Dhafer A. Alzahrani; Enas J. Albokhari; Samaila S. Yaradua; Abidina Abba (Plants, 2021)
This study presents for the first time the complete chloroplast genomes of four medicinal species in the Capparaceae family belonging to two different genera, Cadaba and Maerua (i.e., C. farinosa, C. glandulosa, M. crassifolia and M. oblongifolia), to investigate their evolutionary process and to infer their phylogenetic positions. The four species are considered important medicinal plants, and are used in the treatment of many diseases. In the genus Cadaba, the chloroplast genome ranges from 156,481 bp to 156,560 bp, while that of Maerua ranges from 155,685 bp to 155,436 bp. The chloroplast genome of C. farinosa, M. crassifolia and M. oblongifolia contains 138 genes, while that of C. glandulosa contains 137 genes, comprising 81 protein-coding genes, 31 tRNA genes and 4 rRNA genes. Out of the total genes, 116–117 are unique, while the remaining 19 are replicated in inverted repeat regions. The psbG gene, which encodes for subunit K of NADH dehydrogenase, is absent in C. glandulosa. A total of 249 microsatellites were found in the chloroplast genome of C. farinosa, 251 in C. glandulosa, 227 in M. crassifolia and 233 in M. oblongifolia, the majority of which are mononucleotides A/T found in the intergenic spacer. Comparative analysis revealed variable hotspot regions (atpF, rpoC2, rps19 and ycf1), which can be used as molecular markers for species authentication and as regions for inferring phylogenetic relationships among them, as well as for evolutionary studies. The monophyly of Capparaceae and other families under Brassicales, as well as the phylogenetic positions of the studied species, are highly supported by all the relationships in the phylogenetic tree. The cp genomes reported in this study will provide resources for studying the genetic diversity of Capparaceae, as well as resolving phylogenetic relationships within the family.